SURVEI CEPAT: KARAKTERISTIK & PREVALENSI ANEMIA IBU HAMIL DI KABUPATEN SUKOHARJO TAHUN 2011 - Wibowo, Yudhi; Prihatmo, Wisnuwijoyo (Jurusan Kedokteran FK Unsoed, 2014)
In pregnant women, anemia increases the frequency of complications of pregnancy and childbirth. Maternal mortality in Sukoharjo mainly due to eclampsia 10 cases (47.62%), bleeding in 4 cases (19.05%) and others 7 (33.33%). This rapid survey aims to obtain a picture of the characteristics and prevalence of anemia in pregnant women in Sukoharjo District in 2011. Population of maternal anemia were all pregnant women registered in March 2011. If the assumption that pervalence of maternal anemia in the population of 3.92%, the maximum acceptable in the 95% confidence interval is 10% or 49% upper limit and lower limit of 30%, with a design effect of low category (2), and 1 person per eligible household with 30 clusters in the first stage and seven pregnant women in the second stage of the samples, so respondents of the Rapid Survey are 210. Characteristics of respondents are not or low educated at 45.8%. Families with incomes below the minimum wage by 42.9%, 65.4% of pregnant women did not work, 78.8% of pregnant women get TTD <90 tablets and ANC â¥4 times has only reached 65%. The prevalence of maternal anemia was 51.3% and prevalence of KEK of 24.6%. Most respondents (59.3%) receiving the number of TTDÂ approximately 10 tablets. To improve the health of the mother then the quantity and quality of ANC services improved. Early detection of risk factors more attention. Services are based on the provisions of SOP conformity; and the quantity and quality of TTD improved. TTD should be given a total of 30 tablets at once.Â